A novel shark single-domain antibody targeting OGT as a tool for detection and intracellular localization - Xi, Xiaozhi; Xiao, Guokai; An, Guiqi; Liu, Lin; Liu, Xiaochun; Hao, Peiyu; Wang, Jennifer Yiyang; Song, Dandan; Yu, Wengong; Gu, Yuchao (Frontiers in Immunology, 2023)
Introduction O-GlcNAcylation is a type of reversible post-translational modification on Ser/Thr residues of intracellular proteins in eukaryotic cells, which is generated by the sole O-GlcNAc transferase (OGT) and removed by O-GlcNAcase (OGA). Thousands of proteins, that are involved in various physiological and pathological processes, have been found to be O-GlcNAcylated. However, due to the lack of favorable tools, studies of the O-GlcNAcylation and OGT were impeded. Immunoglobulin new antigen receptor (IgNAR) derived from shark is attractive to research tools, diagnosis and therapeutics. The variable domain of IgNARs (VNARs) have several advantages, such as small size, good stability, low-cost manufacture, and peculiar paratope structure. Methods We obtained shark single domain antibodies targeting OGT by shark immunization, phage display library construction and panning. ELISA and BIACORE were used to assess the affinity of the antibodies to the antigen and three shark single-domain antibodies with high affinity were successfully screened. The three antibodies were assessed for intracellular function by flow cytometry and immunofluorescence co-localization. Results In this study, three anti-OGT VNARs (2D9, 3F7 and 4G2) were obtained by phage display panning. The affinity values were measured using surface plasmon resonance (SPR) that 2D9, 3F7 and 4G2 bound to OGT with KD values of 35.5 nM, 53.4 nM and 89.7 nM, respectively. Then, the VNARs were biotinylated and used for the detection and localization of OGT by ELISA, flow cytometry and immunofluorescence. 2D9, 3F7 and 4G2 were exhibited the EC50 values of 102.1 nM, 40.75 nM and 120.7 nM respectively. VNAR 3F7 was predicted to bind the amino acid residues of Ser375, Phe377, Cys379 and Tyr 380 on OGT. Discussion Our results show that shark single-domain antibodies targeting OGT can be used for in vitro detection and intracellular co-localization of OGT, providing a powerful tool for the study of OGT and O-GlcNAcylation.